Quantifying visual allodynia across migraine subtypes: the Leiden Visual Sensitivity Scale. Issue 11 (November 2018) - Perenboom, Matthijs J.L.; Zamanipoor Najafabadi, Amir H.; Zielman, Ronald; Carpay, Johannes A.; Ferrari, Michel D.
Abstract : Abstract: Enhanced sensitivity to light (photophobia) and patterns is common in migraine and can be regarded as visual allodynia. We aimed to develop and validate a questionnaire to easily quantify sensitivity to light and patterns in large populations, and to assess and compare visual allodynia across different migraine subtypes and states. We developed the Leiden Visual Sensitivity Scale (L-VISS), a 9-item scale (score range 0-36 points), based on literature and patient interviews, and examined its construct validity. Furthermore, we assessed ictal and interictal visual sensitivity in episodic migraine with (n = 67) and without (n = 66) aura and chronic migraine with (n = 20) and without (n = 19) aura, and in healthy controls (n = 86). Differences between migraine subtypes and states were tested using a linear mixed model with 3 fixed factors (episodic/chronic, with/without aura, and ictal/interictal). Test–retest reliability and construct validity of L-VISS were good. Leiden Visual Sensitivity Scale scores correlated in the expected direction with light discomfort (Kendall's τ = −0.25) and pattern glare tests (τ = 0.35). Known-group comparisons confirmed its construct validity. Within migraine subtypes, L-VISS scores were higher in migraine with aura versus without aura and in chronic versus episodic migraine. The linear mixed model showed all factors affected the outcome ( P < 0.001). The L-VISS is an easy-to-use scale to quantify and monitor the burden of bothersome visual sensitivity to light and patterns in large populations. There are remarkable ictal and interictal differences in visual allodynia across migraine subtypes, possibly reflecting dynamic differences in cortical excitability. Abstract : Supplemental Digital Content is Available in the Text.Visual allodynia, the burden of hypersensitivity to light and patterns, is enhanced in migraine patients, particularly in those with migraine with aura and chronic migraine.